Adiponectin/AdipoR Research and Its Implications for Lifestyle-Related Diseases - Iwabu, Masato; Okada-Iwabu, Miki; Yamauchi, Toshimasa; Kadowaki, Takashi (Frontiers in Cardiovascular Medicine, 2019)
The number of patients with obesity continues to increase seriously worldwide. It has become clear that, against a background of insulin resistance, obesity induces the so-called metabolic syndrome consisting of diabetes, dyslipidemia, and hypertension, leading, consequently, to an increased incidence of cardiovascular disease in affected individuals. It is shown that environmental factors, e.g., high-fat diet and lack of physical activity, not only promote the onset of obesity but lead to impairment of the action of adiponectin and its receptors, thus accounting in part for the onset of insulin resistance, type 2 diabetes/metabolic syndrome, and atherosclerosis in modern society. This review is intended to highlight some milestones in adipocyte research from the discovery of the insulin-sensitizing properties of adiponectin to the elucidation of the structures of its receptors, as well as to clarify their therapeutic implications and prospects for lifestyle-related diseases.